PERFORMANCE STUDY OF IRRIGATION NETWORK IN RENGGUNG IRRIGUNG AREA, LOMBOK CENTRAL REGENCY - Restusari Evayanti (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The impact of the decline in irrigation performance is direct and indirect. The direct impact is a decrease in productivity, a decrease in cropping intensity and an increase in farming risk. The indirect impact is the weakening of the farmer's commitment to maintaining the paddy field ecosystem because the poor performance of irrigation makes the land less conducive for farming, especially rice crops. In order to obtain an overview of the condition of the irrigation areas being managed, it is necessary to conduct a study of the irrigation areas, to determine the conditions of irrigation performance and to determine priorities for handling the rehabilitation of irrigation networks and to make policies. DI performance appraisal evaluation results. Renggung is 75.8% where the performance condition of Irrigation Area of Renggung Irrigation is Good Performance.